Histopathological Analysis of Endometrial Biopsies in Abnormal Uterine Bleeding: A Cross-Sectional Study Across Age Groups. - Ashwini Rangappan; Roopa A N; Sharmila P S (Jurnal Ilmu Kesehatan dan Kesehatan, 2025)
Background: Abnormal uterine bleeding (AUB) is a common gynecological complaint among women of reproductive and perimenopausal age, often indicating a wide range of underlying endometrial pathologies. Histopathological examination of endometrial tissue remains the gold standard for determining its etiology and guiding management. Objective: This study aimed to analyze the histopathological patterns of endometrial biopsies in patients presenting with AUB and to correlate these findings with different age groups. Methods: A cross-sectional study was conducted on women presenting with AUB who underwent endometrial biopsy over a defined study period. The specimens were processed and examined microscopically, and histopathological diagnoses were categorized as proliferative, secretory, hyperplastic, atrophic, or neoplastic changes. Data were analyzed according to age distribution and menstrual status. Results: The majority of AUB cases were observed in the perimenopausal group (41–50 years). The most common histopathological finding was proliferative endometrium, followed by secretory and simple hyperplasia without atypia. Endometrial carcinoma and atypical hyperplasia were more frequent in women above 50 years of age. Atrophic and disordered proliferative patterns were also seen in the postmenopausal group. A significant association was found between age and the type of endometrial pathology (p < 0.05). Conclusion: Histopathological evaluation of endometrial biopsies provides critical insights into the etiology of AUB across age groups. Proliferative and hyperplastic changes dominate in perimenopausal women, while malignant lesions are more common in postmenopausal patients. Routine endometrial sampling in AUB cases, particularly among older women, is essential for early detection of premalignant and malignant conditions.